Effects of Salinity and Water Stress Factors on Seed Germination, Early Seedling Growth and Proline Content in an Oil Crop, Black Sesame (Sesamum indicum L.) - Abirami, K.; Vikrant (Journal of Stress Physiology & Biochemistry, 2023)
Present study aims to evaluate the impacts of salinity and water stress factors on seed germination and early seedling growth under ex-vitro conditions in an oil crop, black sesame (Sesamum indicum L., cv. TMV3). During salinity stress, various concentrations of NaCl-solutions (10mM, 25mM, 50mM, 100mM, and 250mM) were employed while during water stress treatments, mannitol and sorbitol solutions in equal concentrations (10mM, 25mM, 50mM, 100mM, 250mM, and 500mM) and polyethylene glycol (PEG) solution (5%, 10%, 15%, 25%, and 50%) were considered. Furthermore, after 3-days and 7-days of stress treatments, observations were recorded as partial and full germination respectively. Results indicate that with 100mM of NaCl solution, sesame seed was found to germinate without root development (80±0.0%) after 7-days of treatments in comparison to control experiment (100±1.0%) and further high concentration (250mM) of NaCl solution was proved to be completely toxic for sesame seed germination. Additionally, seedling growth was also affected with NaCl concentrations and seedling’s height was recorded as minimum with root and shoot lengths (0.5±0.21cm/2.1±0.78cm) in seeds growing with NaCl solution (50mM) while further high concentration (100mM) was proved to be strongly inhibitory for root development in germinated seeds. During water stress treatments, results indicated that mannitol (100mM) turns out to be relatively strong inhibitor for seed germination (50±0.5%) than sorbitol (60±1.0%) with (250mM) solution. However, both mannitol and sorbitol solutions (500mM) were proved to be fully toxic for seed germination. Furthermore, during PEG treatments, PEG solution (25%) was found to be significantly inhibitory and germination frequency (40±0.0%) was recorded while further increase in PEG concentration (50%) was proved to be lethal. Moreover, during early seedling growth, mannitol (100mM) was turned out to be strongly inhibitory for root development and root-shoot length ratio was recorded as (0.0cm/0.25±0.41cm) while sorbitol (100mM) was proved to be slightly weak inhibitor (0.71±0.27cm/0.93±0.32cm). Significantly high concentration of mannitol (250mM) was turned out to be toxic for seedling growth while even very high concentration of sorbitol (500mM) was failed to suppress seedling growth completely. During PEG treatments, the minimum seedling height (0.79±0.31cm/1.43±0.32cm) was recorded with PEG (15%) solution while PEG (25%) solution was found to suppress root formation completely. Furthermore, during endogenous proline content estimation in tissues growing with NaCl salt solutions, results indicated that proline content gradually increases with the increase in NaCl concentrations and was found to be maximum (128.3x10-3g-1) in tissues growing with very high concentration of NaCl (100mM) solution than the tissues growing with very low concentration (10mM) of NaCl salt solution (10.94x10-3g-1).